Hydrogeochemical characteristics and evaluation of groundwater resources of Jilin Province, China - Zeng, Zhaojun; Cui, Yueju; Zhou, Xiaocheng; Pan, Xiaodong; Sun, Fengxia; Liu, Yinan; Tian, Jiao; He, Miao; Zhang, Yongxian; Yan, Yucong; Zou, Zhenyu; Wang, Yuwen; et al. (Frontiers in Water, 2023)
As one of China's nine border provinces, Jilin Province is an important window for China's “Belt and Road” to open up to the north, and an important channel for China's foreign trade and foreign exchanges. Therefore, understanding hydrogeochemical characteristics is very important for effective water resources management in Jilin Province. A total of 64 groundwater samples were collected from 32 monitoring Wells in Jilin Province. Use of hydrogeochemical analysis techniques, WQI index and human health risk index methods to assess hydrogeochemical processes and groundwater quality, including the determination of hydrogeochemical parameters, conventional ions, trace elements and stable isotopes (δD and δ18O). The results show that the groundwater is slightly alkaline, the cations are mainly Na+, Ca2+, Mg2+, and K+, and the anions are mainly HCO3-, Cl−, and SO42-. Most of the groundwater samples belong to Ca-HCO3 and Na-HCO3 types, which are formed by the dissolution of calcite, dolomite, gypsum, silicates and carbonates. Stable isotope analysis shows that groundwater recharge in Jilin mainly comes from atmospheric precipitation at an altitude of 1,430 2,348 m. The strong correlation between trace elements indicates a common source. Most of the groundwater quality index (WQI) in the study area is Class I to Class III, and hazard quotient (HQ) and hazard index (HI) are both below 1. This indicates excellent water quality and minimal health risks associated with human consumption. It is worth noting that trace elements are enriched in the Tanlu fault zone. It provides scientific guidance for the utilization and allocation of groundwater resources in Jilin Province.